Investigations on the slug two-phase flow in horizontal pipes: Past, presents, and future directives - Mohmmed, A.O. (Elsevier Ltd, 2021)
Precise prediction of the gasâliquid slug flow is crucial for proper design and operation at various industrial processes. This paper provides a comprehensive review of published experimental and numerical works in horizontal pipes, including a critical analysis of state-of-the-art parameters used to characterize the slug flow regime. The discussed slug characteristics are slug length, slug frequency, and slug velocity. Throughout the paper, an endeavor does devote to discerning the areas where modern development work is needed. Accordingly, some observed gaps in the literature, comprising hydrodynamic behavior at the transition zone and the interaction between slug flow and structural pipe. The lack of comprehensive laboratory experimental information for high liquid viscosity and the viscosity impact on the slug characteristic is also observed. On the contrary, robust and less empirically independent CFD models are required for accurately predicting the slug characteristics with a minimal computational cost. Â© 2021 Elsevier Ltd